Dependent development, Labour and the Trenton Steel Works, Nova Scotia, c. 1900-1943 - Sandberg, L. (Labour/Le Travailleur, 1991)
Abstract The history of labour at the Trenton Steel Works of the Nova Scotia Steel and Coal Company [Scotia] is explored in the context of dependent development from circa 1900 to 1943. The local owners and managers of Scotia sought profits by aligning themselves with foreign capital and by manufacturing semi-manufactured steel and staples for export. The investment outlook was short-term, few attempts were made to diversity production, and the steel facilities were left to deteriorate already before the contraction of regional and national markets in the 1920s. Before the post-World War I depression, workers at Scotia responded to corporate industrial strategy by resorting to industrial unionism, whose success was aided by a scarcity of labour and the possibility of moving away or moving into small commodity or subsistence production locally. With the post-World War I depression, capital and the state consolidated the Trenton steel works as a technologically obsolescent plant dependent on low-wage, seasonal and part-time labour. The corporate parents, in light of state concessions and favour, could not, however, close the Trenton Works for political reasons. Labour and community interests lobbied hard for industry retention and settled into a work pattern which was aimed at coping with industrial neglect and disinvestment The combination of technological obsolescence, low-wage and seasonal labour was threatened with the formation of a union at the steel works in 1937 and the support of the federal state during the war in levelling wages of Scotia workers with steel workers elsewhere. The labour scarcity during the war provided the political precondition for closure of the rolling mills and nut and bolt plant, the wage increases awarded by the Federal Labour Board served as an excuse while the cause, a conscious corporate strategy of industrial neglect and winding down, was left unchallenged.